قصص أمل من الداخل الجامعة عندما تكون الارادة اقوى من الاعاقة - سندس دلاوي (جامعة محمد بوضياف المسيلة, 2025)
يتناول هذا الروبورتاج واقع الطلبة من ذوي الاحتياجات الخاصةة داخل جامعة المسةيلة، ويسةلط الضةوء على التحديات اليومية التي يواجهونها في بيئة تعليمية ما تزال في طور التكيّف مع احتياجاتهم، رغم المبادرات المحمودة التي تقوم بها الجامعة. ينطلق الروبورتاج من خلفية نظرية وإنسةةةانية تؤكد أن التعليم حق أسةةةاسةةةي يجب أن يُكفل للجميع، دون استثناء. وتُبرز المقدمة أهمية الدمج التربوي، وتحذر من الإقصاء أو التمييز الذي قد يؤثر سلبًا على هةةةذه الفئةةةة. ومن هنةةةا جةةةاء السةةةةةةةؤال المحوري الةةةذي يسةةةةةةةعى العمةةةل للإجةةةابةةةة عنةةةه: "ما هو واقع التعليم لدى طلبة ذوي الاحتياجات الخاصة؟ وما أبرز التحديات التي يواجهونها؟" ينقسم الإطار المنهجي إلى محورين رئيسيين: أسةةةباب ذاتية، تدور حول دافع إنسةةةاني وشةةةخصةةةي لاختيار الموضةةةوع، منها: الوعي بالعدالة التعليمية، الرغبة في إعطاء صوت لمن لا يُسمع، وتجربة شخصية أو قريبة من الواقع المعاش. أسةباب موضةوعية، منها: ارتفاع أعداد الطلبة ذوي الهمم، ضةعف البنية التحتية، قلة الكوادر المختصةة، نقص الوعي المجتمعي، والتمييز داخل الفضاء الجامعي. في الإطار التطبيقي، اعتمدت الصةةةةةةحفية على الملاحظة الميدانية والمقابلات، إذ التقت بطلبة من ذوي الاحتياجات الخاصةةةة، ناقشةةةت معهم مسةةةيرتهم، طموحاتهم، والعقبات التي تعترضةةةهم، مع إشةةةراك الإدارة الجامعية والأساتذة في النقاش لتقييم مدى تطبيق سياسات الدمج والدعم. أما من حيث النوع الصةةةةةةحفي، فتم اختيار الروبورتاج الصةةةةةةحفي الاجتماعي، لقدرته على الجمع بين الجانب التوثيقي والطرح الإنساني. وقد بُني السيناريو الأدبي على تسلسل بصري وموضوعي يبرز حياة هؤلاء الطلبة داخل الجامعة، ويكشةةةةف واقعهم اليومي في التنقل، الدراسةةةةة، المشةةةةاركة، وحتى الإبداع. ويُختتم الروبورتاج برسالة قوية تقول إن الإعاقة ليست نهاية، بل بداية قصة إنسانية مشحونة بالإصرار، وهي دعوة لإعادة النظر في طريقة تعاملنا مع ذوي الاحتياجات، ولتفعيل سةةةةةةياسةةةةةةات دعم حقيقية تراعي كرامتهم وحقهم في تعليم عادل وشامل كلمات المفتاحية: روبرتاج / ذوي الاحتياجات الخاصة / طلبة الجامعة32 reportages sheds light on the reality of students with special needs at M’sila University, highlightng the daily challenges they face in an educatonal environment that is stll adaptng to their needs—despite the commendable eﬀorts made by the insttuton. The report begins with a theoretcal and humanitarian background emphasizing that educaton is a fundamental right that must be guaranteed for all, without excepton. It underlines the importance of inclusive educaton and warns against exclusion and discriminaton, which may negatvely aﬀect this group. This leads to the central queston the report seeks to answer: "What is the current state of educaton for students with special needs, and what are the main challenges they face in the learning environment?" The methodological framework is divided into two main pillars: Personal motvatons, such as a deep sense of social responsibility, belief in educatonal justce, desire to amplify unheard voices, and personal or close experiences with people with disabilites. Objectve reasons, including: the increasing number of students with disabilites, lack of infrastructure and trained staﬀ, insufcient community awareness, and persistent discriminaton within educatonal insttutons. In the applied feldwork, the journalist relied on direct observaton and interviews, meetng with students with disabilites to explore their academic journey, aspiratons, and the barriers they encounter. University administrators and faculty members were also interviewed to assess the implementaton of inclusion policies and support mechanisms. In terms of journalistc format, a social feld reportage was chosen for its ability to blend documentaton with a strong human dimension. The narratve is built visually and thematcally to showcase the daily life of these students on campus—revealing not only their difcultes but also their resilience, talents, and drive to succeed. The reportage concludes with a strong message: disability is not an end, but rather the beginning of a deeply human story driven by determinaton. It is a call to reconsider how we view and treat people with disabilites, and to implement real support policies that respect their dignity and right to equitable, inclusive educaton.